Cataloging as a method of work of Old Polish writers - Wichowa, Maria (Philology as the Ordering of Chaos: Language and Text Studies. Ad honorem Professoris Marci Cybulski, 2018)
The creators of literature already in ancient times appreciated the utility of cataloging as a method of collecting and developing the material. In the Old Polish era this technique was used on a large scale. The authors wrote down such registers for several reasons. These activities were aimed at organizing the material. It was a method of presenting the world, showing the richness of its elements through their collection, enumeration, hierarchization. Sometimes the catalog was also a creative principle of the literary concept, a way of surprise and amazement of the reader. Cataloging was a useful method of gathering and developing material both in the area of literature with high artistic value, in poetry and in the utilitary literature, in historical and encyclopedic works.